PENGEMBANGAN PERMAINAN WHO WANTS TO BE A GREAT CHEMIST? SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN KIMIA DI SMA - Muhammad Hizbul W, J. Fendra N, Cahya Dwi W & Aditya Yanuar R (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
Today teaching tends to be integrated with information technology and the use ofEnglish becomes important. Chemistry is an abstract subject so that it is difficult to understandand even lower the students’ interest and learning achievement. Games can be integratedin the teaching. The research is aimed at developing and revealing the quality of the gameWho Wants to be a Great Chemist? As alternative media in the teaching of chemistry insenior high schools.The research applied the procedural model. This development involved four steps:constructing test items, validating test items, developing the software and evaluating theproduct, which was the game Who Wants to be a Great Chemist? In the form of softwareprogrammed by using Adobe Flash CS3. the evaluation was done by 5 senior high schoolstudents. The data in this research are descriptive ones in the form of 1) the data about theprocess of the product development in line with the procedure implemented; 2) the dataabout the quality of the product.The results of the research are the development of the off line game Who Wants tobe a Great Chemist? By using Adobe Flash CS3 with the start menu, instructions, materials,TPU, and profile. The on line version with the domain www.greatchemist.com was developedby using the program of joomla V.1.5.15. 240 test items for grade X, 210 test items for gradeXI, and 180 test items for year XII were developed. In terms of the quality of the game WhoWants to be a Great Chemist?, in the aspects of A, B, and C the game is classified as good orclear with the scores 39.6; 16.6; and 36.4 respectively.Keywords: game, Who Wants to be a Great Chemist?, teaching media